(untitled) (Vallis Aurea, 2024)
Good governance is an unanswered area, the eternal search for optimal social order. Throughout time, good governance changed its appearance depending on many elements (political, economic, social, legal, moral, etc.). Good governance implies a responsibility of authority at all levels, respecting guaranteed rights and freedoms The paper analyses executive authority in some countries of Southeast Europe. And how they exist concerning executive power at the local level and towards citizens. The normativity, comparative, historical method and methods of analysis and synthesis were used.